ANALYSIS OF CHANGES IN COAST LINE USING LANDSAT IMAGERY AT NORTH SIPORA DISTRICT OF MENTAWAI REGENCY, WEST SUMATERA PROVINCE - Ulfa Rahmi; Musrifin Galib; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstrackChanges in the coastline are, back and forth events coastline than before that causad by natural and human factors. This research was conducted in August 2018 in the coastal area of North Siporadistrict, West Sumatera Province. This study aims to determine changes in the coastline in North Sipora District use Landsat Imagery, year 2000. 2007, 2013, and 2018. Image data was downloaded from the USGS site was then analyzed using the ER Mapper 7.0 application and Arc Gis. The results of image data processing show that coastline changes that occurred during the 18 years experienced changes an accretion and abrassions.Based on image data processing, the area with high accretion is found in 2000-2007 with an area of 571 ha and a high area of abrassion in 2007-2013 with an area of 271 ha. On measurements in the field the abrassion speeds obtained ranged from 1.4-1.76 m / year. The highest abrassion speed is found on Mappadegat Beach.Keywords: Coastline, North Sipora, Landsat Imagery, Abrassion, Accretion